Repair work, resistance and the invisible data labour of Lebanon's digital humanitarian infrastructures - Jenna Imad Harb (Big Data & Society)
This article draws upon a multi-sited ethnography of everyday labour in Lebanon's digital cash assistance for Syrian refugees. The datafication of humanitarian infrastructures generates technological breakdown, gaps in data and incredibly strict and cumbersome rules. In response to impediments related to biometric identification and automated poverty targeting, this article argues that humanitarian staff, refugee recipients and community members engage in ‘repair work’ – the subtle and quotidian labour that goes into addressing fragility and maintaining functionality. Inspired by feminist studies of labour, repair work is found to be invisible in being undervalued, unpaid and reproductive, which is reminiscent of labour that has historically fallen to disenfranchised people. Repair work also enables data workers to assert their autonomy and contest infrastructures that they framed as being unreasonable and unjust. In doing so, findings suggest that repair work is fundamental to the ability of data-driven aid programmes to cater to the needs of populations in crisis. This paper marks two contributions to understanding the promise and perils of ‘Technology for Good’: it introduces repair work as a novel conceptual framework to analyse labour involved in the datafication of aid, and it applies new empirical evidence to critical studies of data work.